2020
DOI: 10.1158/1078-0432.ccr-19-3373
|View full text |Cite
|
Sign up to set email alerts
|

Wee1 Kinase Inhibitor AZD1775 Effectively Sensitizes Esophageal Cancer to Radiotherapy

Abstract: Purpose: Esophageal cancer is a deadly malignancy with a 5-year survival rate of only 5% to 20%, which has remained unchanged for decades. Esophageal cancer possesses a high frequency of TP53 mutations leading to dysfunctional G 1 cell-cycle checkpoint, which likely makes esophageal cancer cells highly reliant upon G 2 -M checkpoint for adaptation to DNA replication stress and DNA damage after radiation. We aim to explore whether targeting Wee1 kinase to abolish G 2 -M checkpoint sensitizes esophageal cancer c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 65 publications
1
28
0
Order By: Relevance
“…Experimental evidence has demonstrated that Wee1 inhibitor AZD1775 significantly inhibits cancer growth and impairs RAD51 focus formation in response to radiotherapy 394 . The mechanisms underlying how inhibition of the Wee1 activity by AZD1775, resulting in promotion of the G2/M transition, is to be considered 395 . In this context, cancer cells, which harbor G1 checkpoint aberrations, could enter premature mitosis; ultimately, mitotic catastrophe would occur because of this unsuccessful DDR 388 .…”
Section: Targeting Dna Damage Repair To Sensitize Cancer Cells To Radiationmentioning
confidence: 99%
“…Experimental evidence has demonstrated that Wee1 inhibitor AZD1775 significantly inhibits cancer growth and impairs RAD51 focus formation in response to radiotherapy 394 . The mechanisms underlying how inhibition of the Wee1 activity by AZD1775, resulting in promotion of the G2/M transition, is to be considered 395 . In this context, cancer cells, which harbor G1 checkpoint aberrations, could enter premature mitosis; ultimately, mitotic catastrophe would occur because of this unsuccessful DDR 388 .…”
Section: Targeting Dna Damage Repair To Sensitize Cancer Cells To Radiationmentioning
confidence: 99%
“…Adavosertib potentiates the activity of other DNA damage-inducing agents in preclinical models (10)(11)(12)(13), which has prompted several recent clinical trials (14)(15)(16)(17)(18). Adavosertib also acts as a radiosensitizer, enhancing radiation-induced DNA damage in vivo (19).…”
Section: Introductionmentioning
confidence: 99%
“…Wee1 has been reported to be highly expressed in numerous malignancies including breast, hepatocellular, lung, melanoma, and others ( 33 ). To assess the role of Wee1, we utilized the Wee1 inhibitor MK-1775 (adavosertib, AZD1775), which has been evaluated in numerous preclinical and clinical trials as single agent or in combination, often with DNA damaging agents ( 41 43 ). Notably, recent reports have highlighted synergistic potential for MK-1775 in combination with other kinase inhibitors, including TAK228 ( 34 ) and alisertib ( 35 ).…”
Section: Discussionmentioning
confidence: 99%